Kamisama kiss. Vol. 4 - Suzuki, Julietta (VIZ Media, 2011)
"Nanami Momozono is alone and homeless after her dad skips town to evade his gambling debts and the debt collectors kick her out of her apartment. So when a man she's just saved from a dog offers her his home, she jumps at the opportunity. But it turns out his place is a shrine, and Nanami has unwittingly taken over his job as a local deity. Nanami has all kinds of new responsibilities she doesn't understand, dangers she's unaware of, and a cranky ex-familiar who's ... actually pretty hot. What's a new-fledged godling to do?"